2020
DOI: 10.32539/jkk.v7i3.11133
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara Tingkat Kecemasan dengan Kualitas Tidur pada Ibu Hamil Primigravida Trimester III di Rumah Sakit Bersalin Jeumpa Kota Pontianak

Abstract: Background Anxiety is an emotional condition characterized by tension, fear and anxiety, accompanied by somatic symptoms (headache, sweating, palpitation, chest tightness, and mild stomach upset), which is one of the psychological aspect affecting pregnancy, especially primigravida pregnancy. Anxiety stimulates the body to be difficult to relax in pregnant woman that can cause the decrease of sleep duration resulting in sleep disturbance. The objective of this study was to assess the relationship between anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A previous study conducted in Pontianak, Indonesia on third trimester primigravida women found a significant relationship between anxiety levels and sleep quality in primigravida pregnant women in the third trimester [9]. Other studies also showed a strong and positive relationship between anxiety levels and sleep quality in third trimester pregnant women [10,11]. Meanwhile, the results of other studies showed there was no relationship between anxiety in facing childbirth and sleep quality of third trimester pregnant women [12].…”
Section: Introductionmentioning
confidence: 93%
“…A previous study conducted in Pontianak, Indonesia on third trimester primigravida women found a significant relationship between anxiety levels and sleep quality in primigravida pregnant women in the third trimester [9]. Other studies also showed a strong and positive relationship between anxiety levels and sleep quality in third trimester pregnant women [10,11]. Meanwhile, the results of other studies showed there was no relationship between anxiety in facing childbirth and sleep quality of third trimester pregnant women [12].…”
Section: Introductionmentioning
confidence: 93%